Teachers' perceptions of challenges in online learning: Voices from secondary EFL teachers - Dwi Bayu Saputra; Honesty Yonanda Ayudhia; Reci Muswari (JOALL (Journal of Applied Linguistics and Literature), 2022)
The abrupt change from a traditional classroom to online learning must have produced some issues, and many scholars were drawn in to investigate the reported challenges during online learning. There is, however, a paucity of research on secondary EFL teachers' perceptions of online learning challenges, notably in four major areas: technology use, instruction, assessment, and students. Therefore, the purpose of this descriptive quantitative study is to examine secondary EFL teachers' perspectives of the challenges they encounter in dealing with the aforementioned issues.  The participants included 73 upper and lower secondary English as a foreign language (EFL) teacher. A closed-item questionnaire was deployed, with a total of 38 items addressing issues related to online learning challenges. The findings reveal that secondary EFL teachers in Indonesia reported medium-level challenges in teaching EFL online in terms of technology use, instruction, assessment, and students, whilst challenges in assessing students in online learning were identified as the highest. The results contribute to the advancement of English language education by providing literature on the development of EFL teachers.